Recurrent Bilateral Staghorn Stones as a Manifestation of Primary Hyperparathyroidism due to Parathyroid Adenoma - Laurentius A Pramono; Deka Larasati; Yosephine Yossy; Dante S Harbuwono; Suharko Soebardi (Acta Medica Indonesiana)
Primary hyperparathyroidism is a medical condition caused by overactive of parathyroid gland. It is most commonly caused by solitary adenoma of the parathyroid gland. Other causes of this condition are hyperplasia, multiple adenomas, and parathyroid cancer. Primary hyperparathyroidism has some metabolic consequences in the calcium metabolism. Hypercalcemia in patient with primary hyperparathyroidism will resulted to the most important comorbidity that is chronic deposition of calcium in the kidney forming nephrolithiasis or other urolithiasis. It is not uncommon, patient with parathyroid adenoma come to health care professionals with the chief complain of recurrence nephrolithiasis.